Still waters can be sickening - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
The article on wetlands ecosystems in Spore 100 focused on their multiple uses and how they could be better managed and conserved for future generations.